2022
DOI: 10.3389/fvets.2022.907369
|View full text |Cite
|
Sign up to set email alerts
|

Improved Whole Gamma Irradiated Avian Influenza Subtype H9N2 Virus Vaccine Using Trehalose and Optimization of Vaccination Regime on Broiler Chicken

Abstract: Gamma (γ)-radiation can target viral genome replication and preserve viral structural proteins compared to formalin inactivation. Thus, a stronger immunity could be induced after the inoculation of the irradiated virus. In this study, γ-irradiated low-pathogenic avian influenza virus-H9N2 (LPAIV-H9N2) was used to immunize the broiler chicken in two formulations, including γ-irradiated LPAIV-H9N2 with 20% Trehalose intranasally (IVT.IN) or γ-irradiated LPAIV-H9N2 plus Montanide oil adjuvant ISA70 subcutaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…In fact, CD8 T cells were stimulated following vaccination of mice with the irradiated virus, recognizing the MHC class I-restricted ASNETNMETM peptide of the nucleoprotein. Notably, this finding is in line with the finding of Motamedi Sedeh et al that cell-mediated immune responses stimulated following immunization with irradiated vaccine candidates were prior to those observed following vaccination using chemically inactivated viruses [48]. Similar results were obtained when chickens were immunized to compare irradiated and formalin-treated vaccine candidates [43].…”
Section: Discussionsupporting
confidence: 88%
“…In fact, CD8 T cells were stimulated following vaccination of mice with the irradiated virus, recognizing the MHC class I-restricted ASNETNMETM peptide of the nucleoprotein. Notably, this finding is in line with the finding of Motamedi Sedeh et al that cell-mediated immune responses stimulated following immunization with irradiated vaccine candidates were prior to those observed following vaccination using chemically inactivated viruses [48]. Similar results were obtained when chickens were immunized to compare irradiated and formalin-treated vaccine candidates [43].…”
Section: Discussionsupporting
confidence: 88%
“…At present, inactivated H9N2 vaccines have demonstrated high efficacy in protecting against clinical disease, but variable results have also been observed in reducing the mortality and the level of viral shedding in chickens. It was reported that H9N2 AIV causes no death in chicken after intranasal challenge in control group [ 46 ] and no virus shedding in inactivated vaccine vaccination group [ 47 ]. However, other studies have shown that H9N2 AIV can cause death in chicken after intranasal challenge [ 48 50 ], and intranasal challenge of H9N2 virus resulted in different degrees of virus shedding in the inactivated vaccine group [ 46 , 50 52 ], which was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The BrdU kit allows accurate assessment of cell proliferation by measuring BrdU incorporation into newly synthesized cellular DNA. Absorbance was measured at 450 nm, and the stimulation index (SI) was calculated as the mean OD of three wells corresponding to cells stimulated with an antigen divided by the mean OD of the triple-negative control wells [13,17,19].…”
Section: Spleen Lymphocyte Proliferation (Slp) Responsementioning
confidence: 99%